Evaluation of Healthcare Economics of OECD _x000D_ Countries: Multi-Objective Statistical Optimization _x000D_ Model - (:unkn) unknown (My University, 2021)
Healthcare systems comprise the most crucial factors affecting countries economically. In this study, the _x000D_ infrastructure and economic structure of healthcare systems belonging to the Organization for Economic _x000D_ Co-operation and Development (OECD) countries are discussed to evaluate the healthcare expenditures _x000D_ (HE) and healthcare expenditures per capita (pcHE) of OECD members. We have identified factors related _x000D_ to healthcare economics and analyzed the significance ratios of these factors to calculate the feasible values _x000D_ of the factors affecting the healthcare systems in the OECD members by statistical optimization analysis. _x000D_ Within the feasible values obtained by using a multi-objective optimization model (MOOM) because of _x000D_ statistical analysis, the HE of OECD countries was minimized, and an improvement of 29.13% was achieved. _x000D_ The second objective function aimed to maximize the pcHE that was estimated to be at least $5,282.37 for _x000D_ the OECD members. Consequently, in countries that do not have a social healthcare system, it is perceived _x000D_ that HE amounts are excessive. The fundamental reason for this situation represents the healthcare sector’s _x000D_ perception as a business in those countries.

Sağlık sistemleri, ülke ekonomilerini etkileyen en önemli faktörlerden birdir. Bu çalışmada, OECD _x000D_ üyelerinin sağlık harcamalarını (SH) ve kişi başına düşen sağlık harcamalarını (kbSH) değerlendirmek için _x000D_ Ekonomik İşbirliği ve Kalkınma Teşkilatı (OECD) ülkelerine ait sağlık sistemlerinin altyapısı ve ekonomik _x000D_ yapısı tartışılmıştır. İstatistiksel optimizasyon analizi ile OECD üyelerindeki sağlık sistemlerini etkileyen _x000D_ faktörlerin uygulanabilir değerlerini hesaplamak için sağlık ekonomisi ile ilgili faktörleri belirlenerek, bu _x000D_ faktörlerin önemlilik oranlarını analiz ettik. İstatistiksel analiz aracılığıyla çok amaçlı optimizasyon modeli _x000D_ (MOOM) kullanılarak elde edilen uygulanabilir değerler içerisinde OECD ülkelerinin SH’si minimize _x000D_ edilmiş ve % 29,13 oranında iyileşme sağlanmıştır. İkinci amaç fonksiyonu ise OECD üyeleri için kbSH’yi _x000D_ maksimize etmek amacıyla en az kbSH değeri 5.282,37 dolar olarak tahmin edilmiştir. Sonuç olarak sosyal _x000D_ sağlık sistemi olmayan ülkelerde SH miktarlarının aşırı olduğu algılanmaktadır. Bu durumun temel nedeni, _x000D_ sağlık sektörünün o ülkelerdeki bir işletme olarak algılanmaktadır.
OECD Ülkelerine ait Sağlık Ekonomilerinin Değerlendirilmesi: Çok Amaçlı İstatistiksel Optimizasyon Modeli